WORKSHOP “PETANI PERKOTAAN” BERKEBUN ASYIK DENGAN HIDROPONIK - Wahyuningsih, Panca; Rahman, Faisal Riza; Kartika, Daniel Adhi; Efendi, Khusnan; Hidayat, M. Ibnu (STIE Pelita Nusantara, 2024)
This community service workshop titled